Pengaruh Supervisi Kepala Sekolah dan Motivasi Guru Terhadap Kinerja Guru di SMA Negeri 1 Tondano - Rasu, Zeslie Marlin; Tuerah, Philoteus E. A; Usoh, Elni J. (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted with the aim of determining the influence of principal supervision on teacher performance, the influence of teacher motivation on teacher performance, and the influence of principal supervision and teacher motivation simultaneously on teacher performance. In this research, quantitative research methods were used with a sample size of 36 respondents, namely teachers at SMA Negeri 1 Tondano. The data in this study were analyzed using multiple linear regression analysis, and testing the hypothesis was carried out in two ways, namely partial tests and simultaneous tests. Apart from knowing the influence between variables, this research also includes a correlation coefficient test which functions to see how big the relationship between variables is and a coefficient of determination test to find out how big their contribution is. The results obtained in this research are that there is a significant influence, both partially and simultaneously, of the principal supervision variables (X1) and teacher motivation (X2) on teacher performance (Y), this means that when there is an increase or decrease in school principal supervision and Teacher Motivation, it will also have an impact on increasing or decreasing Teacher Performance